Financial Ratio Adjustment: Industry-Wide Effects or Strategic Management - WU, Chunchi (Institutional Knowledge at Singapore Management University, 1997)
This paper proposes an alternative model for analyzing financial ratio behavior. The model postulates that (1) firms' financial ratios reflect unexpected changes in industry conditions; and (2) managers attempt to move their financial ratio toward the long-run desirable target. This model is employed to assess the relative weights of financial ratio movement that are associated with these two forces. The results show that changes in financial ratios can be due to both external shocks and strategic adjustment by management. The amount of financial ratio smoothing due to strategic adjustment appears to be substantial. Furthermore, the speed of convergence toward the optimal targets varies across industries and firms of different size.